β-Thalassemia and Diabetes Mellitus: Current State and Future Directions - Taneera, Jalal; Mahgoub, Eglal; Qannita, Reem; Alalami, Ayah; Shehadat, Ola Al; Youssef, Mona; Dib, Ayah; Hajji, Alaa Al; Hajji, Amani Al; Al-Khaja, Fatheya; Dewedar, Hany; Hamad, Mawieh (Hormone and Metabolic Research, 2023)
β-Thalassemia major is a congenital hemoglobin disorder that requires regular blood transfusion. The disease is often associated with iron overload and diabetes mellitus, among other complications. Pancreatic iron overload in β-thalassemia patients disrupts β-cell function and insulin secretion and induces insulin resistance. Several risk factors, including family history of diabetes, sedentary lifestyle, obesity, gender, and advanced age increase the risk of diabetes in β-thalassemia patients. Precautionary measures such as blood glucose monitoring, anti-diabetic medications, and healthy living in β-thalassemia patients notwithstanding, the prevalence of diabetes in β-thalassemia patients continues to rise. This review aims to address the relationship between β-thalassemia and diabetes in an attempt to understand how the pathology and management of β-thalassemia precipitate diabetes mellitus. The possible employment of surrogate biomarkers for early prediction and intervention is discussed. More work is still needed to better understand the molecular mechanism(s) underlying the link between β-thalassemia and diabetes and to identify novel prognostic and therapeutic targets.
Keywords: thalassemia; United Arab Emirates; biomarkers; diabetes